Chemically strengthened microcrystalline glass and preparation method thereof
By introducing a composite structure of Boltzmann distributed crystal layers and uniformly distributed crystal layers into microcrystalline glass and combining it with ion exchange treatment, the problem of uneven stress distribution after chemical strengthening of microcrystalline glass was solved, and its mechanical properties and impact resistance were improved.
Patent Information
- Application Number
- CN202510559195.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-09-26
AI Technical Summary
After chemical strengthening, the surface stress distribution of existing microcrystalline glass is uneven, the edges are prone to warping and stress relaxation, resulting in poor mechanical properties.
A composite structure of Boltzmann distributed crystal layers and uniformly distributed crystal layers is adopted. By introducing a Boltzmann gradient distributed crystal phase into the microcrystalline glass and combining it with ion exchange treatment, a stress distribution combining compressive stress and tensile stress is formed to optimize the stress gradient.
The uniformity of stress distribution on the surface of microcrystalline glass is achieved, edge warping and stress relaxation are avoided, and the mechanical properties of the glass, especially the impact strength and fracture toughness, are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of material technology, and in particular to the field of glass-ceramics technology. Specifically, the present application discloses a chemically strengthened glass-ceramics and a preparation method thereof. Background Art
[0002] Glass-ceramics contain tiny crystals that are inherently strong and can inhibit crack propagation when impacted. This gives glass-ceramics superior mechanical properties compared to ordinary glass, resulting in superior drop resistance. Glass-ceramics has experienced rapid development since the turn of the century, with particular growth in recent years for mobile phone covers. Due to its high strength and drop resistance, glass-ceramics has become increasingly popular in the consumer electronics market.
[0003] The finished microcrystalline glass products currently on the market need to undergo chemical strengthening (also known as ion exchange strengthening) to significantly improve the surface stress, bending strength and other mechanical properties of the microcrystalline glass, so as to better withstand external force impact and reduce the risk of breakage during use; however, due to the interface effect between the crystal phase and the glass phase and the complexity of the ion exchange process, the surface stress distribution of the chemically strengthened microcrystalline glass is uneven, the edges are prone to warping and stress relaxation, and the mechanical properties are poor.
[0004] It is important to note that the techniques described in this section are not necessarily those that have been previously conceived or employed. Unless otherwise indicated, it should not be assumed that any technique described in this section is prior art simply because it is included in this section. Similarly, unless otherwise indicated, the issues mentioned in this section should not be considered to have been recognized as prior art. Summary of the Invention
[0005] The present application provides a chemically strengthened microcrystalline glass and a preparation method thereof, aiming to solve one of the problems in the related art at least to a certain extent.
[0006] In a first aspect, the present application provides a chemically strengthened microcrystalline glass, which includes two Boltzmann distributed crystal layers extending inward from two outer surfaces with a preset thickness, and a uniformly distributed crystal layer located between the two Boltzmann distributed crystal layers, wherein the thickness of each Boltzmann distributed crystal layer is greater than 0 and less than or equal to 200 μm; the crystal ratio of each Boltzmann distributed crystal layer gradually increases from the outer surface to the inner part of the chemically strengthened microcrystalline glass, and the maximum crystal ratio of the Boltzmann distributed crystal layer is 50% to 89%, and the minimum crystal ratio is 30% to 65%.
[0007] Optionally, at least a portion of the Boltzmann distribution crystal layer has compressive stress, and the compressive stress is greater than 0 and less than or equal to 270 MPa.
[0008] Optionally, the thickness of each Boltzmann distribution crystal layer is 100-200 μm.
[0009] Optionally, a measurement tolerance of the crystal ratio in the uniformly distributed crystal layer is ±5%.
[0010] Optionally, the uniformly distributed crystal layer has tensile stress, and a tensile stress line density CTLD thereof is greater than or equal to 26000 MPa.
[0011] Optionally, the crystalline phase of the chemically strengthened glass-ceramics includes at least one of lithium disilicate, petalite, lithium metasilicate, and spodumene.
[0012] Optionally, the chemically strengthened glass-ceramics is obtained by subjecting glass-ceramics of preset components to ion exchange treatment, and the components of the glass-ceramics, expressed in molar percentage, include:
[0013] SiO2 greater than or equal to 60% and less than or equal to 78%;
[0014] 1.5% or more and 6.7% or less of Al2O3;
[0015] 16% or more and 26.8% or less of Li2O;
[0016] P2O5 greater than or equal to 0.1 and less than or equal to 2.5%;
[0017] ZrO2 greater than or equal to 0 and less than or equal to 5%;
[0018] RO is greater than or equal to 0 and less than or equal to 5.3%, and RO includes at least one of CaO, MgO, ZnO, and BaO;
[0019] greater than or equal to 0% and less than or equal to 6.5% Na2O;
[0020] K2O greater than or equal to 0 and less than or equal to 4%;
[0021] Greater than or equal to 0 and less than or equal to 1% of clarifier.
[0022] Optionally, the chemically strengthened glass-ceramics satisfies the following crystal content relationship:
[0023] F(x)=W*(-a*(T*t) / (1+exp((x i -x0) / (dx)))
[0024] Wherein, F(x) represents the crystal ratio of the chemically strengthened glass-ceramics at depth x, W represents the crystal content of the chemically strengthened glass-ceramics before strengthening, a is a constant, T represents the temperature of the chemical strengthening salt bath, t represents the duration of the ion exchange treatment, and x i represents the depth from the glass surface to i, x0 represents the depth of the glass surface; and, 20%<F(x)<75%, 30% <W<75%,0<a<0.001,0<x i <250μm.
[0025] Optionally, the chemically strengthened glass-ceramics satisfies the following tensile stress linear density relationship:
[0026] CTLD=A*E / (2*(1-2ν))*Δv%-B*CS / τ
[0027] Where F represents the tensile stress linear density, A and B are constants, E represents Young's modulus, ν represents Poisson's ratio, △v% represents the volume change ratio of the glass before and after chemical strengthening, CS represents the surface compressive stress, τ represents the relaxation time; and, 26000≤F≤34000MPa, 97≤E≤105GPa, 0<△v%<3%, 0≤τ≤1750h, 60 <A+B<80。
[0028] Optionally, the chemically strengthened glass-ceramics is obtained by subjecting glass-ceramics of preset components to ion exchange treatment, and the components of the glass-ceramics, expressed in molar percentage, include:
[0029] SiO2 greater than or equal to 60% and less than or equal to 78%;
[0030] Al2O3 greater than or equal to 2% and less than or equal to 6.7%;
[0031] 16% or more and 24% or less of Li2O;
[0032] P2O5 greater than or equal to 0.1 and less than or equal to 2.2%;
[0033] ZrO2 greater than or equal to 0 and less than or equal to 5%;
[0034] RO is greater than or equal to 0 and less than or equal to 5.3%, and RO includes at least one of CaO, MgO, ZnO, and BaO;
[0035] greater than or equal to 0% and less than or equal to 5% Na2O;
[0036] K2O greater than or equal to 0 and less than or equal to 4%;
[0037] Greater than or equal to 0 and less than or equal to 1% of clarifier.
[0038] Optionally, the chemically strengthened glass-ceramics is obtained by subjecting glass-ceramics of preset components to ion exchange treatment, and the components of the glass-ceramics, expressed in molar percentage, include:
[0039] SiO2 greater than or equal to 60% and less than or equal to 78%;
[0040] 1.5% or more and 5.5% or less of Al2O3;
[0041] 18% or more and 26.8% or less of Li2O;
[0042] P2O5 greater than or equal to 0.1 and less than or equal to 2.5%;
[0043] ZrO2 greater than or equal to 0 and less than or equal to 5%;
[0044] RO is greater than or equal to 0 and less than or equal to 3.4%, and RO includes at least one of CaO, MgO, ZnO, and BaO;
[0045] greater than or equal to 0% and less than or equal to 6.5% Na2O;
[0046] K2O greater than or equal to 0 and less than or equal to 4%;
[0047] Greater than or equal to 0 and less than or equal to 1% of clarifier.
[0048] Optionally, the crystalline phase of the chemically strengthened glass-ceramics includes lithium disilicate and petalite.
[0049] Optionally, the maximum ratio of lithium disilicate crystals in the Boltzmann distribution crystal layer is 33% to 39%, and the minimum ratio of lithium disilicate crystals is 20% to 24%, and the maximum ratio of petalite crystals in the Boltzmann distribution crystal layer is 47% to 50%, and the minimum ratio of petalite crystals is 34% to 38%.
[0050] Optionally, the average grain size of the lithium disilicate crystal phase is less than or equal to 32.5-39.3 nm, the average grain size of the petalite crystal phase is less than or equal to 24.6-29.1 nm, and the crystallinity is greater than or equal to 84.72%.
[0051] Optionally, the lithium disilicate crystalline phase meets the following indicators: the size of 98% of the grains in the lithium disilicate crystalline phase as a whole is less than or equal to 55 nm, the size of 95% of the grains in the lithium disilicate crystalline phase as a whole is less than or equal to 50 nm, and the size of 80% of the grains in the lithium disilicate crystalline phase as a whole is less than or equal to 45 nm;
[0052] The petalite crystalline phase meets the following indicators: 98% of the grains in the petalite crystalline phase have a size of less than or equal to 45 nm, 95% of the grains in the petalite crystalline phase have a size of less than or equal to 40 nm, and 80% of the grains in the petalite crystalline phase have a size of less than or equal to 30 nm;
[0053] The crystallinity is greater than or equal to 85.8%.
[0054] Optionally, the crystalline phase of the chemically strengthened glass-ceramics is lithium disilicate.
[0055] Optionally, the maximum ratio of lithium disilicate crystals in the Boltzmann distribution crystal layer is 50% to 75%, and the minimum ratio of lithium disilicate crystals is 61% to 65%.
[0056] Optionally, the lithium disilicate crystal phase meets the following indicators: an average grain size is less than or equal to 38 to 45.7 nm, and a crystallinity is greater than or equal to 56.38%.
[0057] Optionally, the lithium disilicate crystalline phase meets the following indicators: the size of 98% of the grains in the overall crystalline phase is less than or equal to 60 nm, the size of 95% of the grains in the overall crystalline phase is less than or equal to 55 nm, and the size of 80% of the grains in the overall crystalline phase is less than or equal to 50 nm; the crystallinity is greater than or equal to 61.22%.
[0058] Optionally, the chemically strengthened glass-ceramics satisfies the following crystal content relationship:
[0059] F(x)=W*(-a*(T*t) / (1+exp((x i -x0) / (dx)))
[0060] Wherein, F(x) represents the crystal ratio of the chemically strengthened glass-ceramics at depth x, W represents the crystal content of the chemically strengthened glass-ceramics before strengthening, a is a constant, T represents the temperature of the chemical strengthening salt bath, t represents the duration of the ion exchange treatment, and x i represents the depth from the glass surface to i, x0 represents the depth of the glass surface; and, 20%<F(x)<50%, 30% <W<50%,0<a<0.001,0<x i <250μm.
[0061] Optionally, the chemically strengthened glass-ceramics satisfies the following crystal content relationship:
[0062] F(x)=W*(-a*(T*t) / (1+exp((x i -x0) / (dx)))
[0063] Wherein, F(x) represents the crystal ratio of the chemically strengthened glass-ceramics at depth x, W represents the crystal content of the chemically strengthened glass-ceramics before strengthening, a is a constant, T represents the temperature of the chemical strengthening salt bath, t represents the duration of the ion exchange treatment, and x i represents the depth from the glass surface to i, x0 represents the depth of the glass surface; and, 55%<F(x)<75%, 65% <W<75%,0<a<0.001,0<x i <250μm.
[0064] Optionally, the chemically strengthened glass-ceramics satisfies the following tensile stress linear density relationship:
[0065] CTLD=A*E / (2*(1-2ν))*Δv%-B*CS / τ
[0066] Wherein, CTLD represents tensile stress linear density, A and B are constants, E represents Young's modulus, ν represents Poisson's ratio, △v% represents the volume change ratio of glass before and after chemical strengthening, CS represents surface compressive stress, τ represents relaxation time; and, 26000≤F≤30000MPa, 97≤E≤105GPa, 0<△v%<3%, 0.6≤τ≤28h, 60 <A+B<80。
[0067] Optionally, the chemically strengthened glass-ceramics satisfies the following tensile stress linear density relationship:
[0068] CTLD=A*E / (2*(1-2ν))*Δv%-B*CS / τ
[0069] Where F represents the tensile stress linear density, A and B are constants, E represents Young's modulus, ν represents Poisson's ratio, △v% represents the volume change ratio of the glass before and after chemical strengthening, CS represents the surface compressive stress, τ represents the relaxation time; and, 31000≤F≤34000MPa, 97≤E≤105GPa, 0<△v%<3%, 0.6≤τ≤28h, 60 <A+B<80。
[0070] A second aspect of the present application provides a method for preparing chemically strengthened glass-ceramics, comprising:
[0071] The raw materials are mixed evenly according to the glass formula, melted at the preset melting temperature and melting time, and then formed and annealed to obtain the glass raw material;
[0072] heat-treating the glass raw material to obtain glass-ceramics;
[0073] The glass-ceramics is immersed in a chemically strengthened salt bath for ion exchange treatment to obtain a chemically strengthened glass-ceramics; wherein the chemically strengthened glass-ceramics includes two Boltzmann distribution crystal layers extending inward from two outer surfaces with a preset thickness, and a uniformly distributed crystal layer located between the two Boltzmann distribution crystal layers, and the thickness of each Boltzmann distribution crystal layer is greater than 0 and less than or equal to 200 μm; the crystal ratio of each Boltzmann distribution crystal layer gradually increases from the outer surface to the inner part of the chemically strengthened glass-ceramics, and the maximum crystal ratio of the Boltzmann distribution crystal layer is 50% to 89%, and the minimum crystal ratio is 30% to 65%.
[0074] Optionally, the chemical strengthening salt bath comprises, by mass percentage: greater than or equal to 9.99% and less than or equal to 39.99% of KNO3, greater than or equal to 59.99% and less than or equal to 89.99% of NaNO3, and greater than or equal to 0.03% and less than or equal to 0.1% of LiNO3.
[0075] Optionally, the temperature of the chemical strengthening salt bath is 390-600° C., and the duration of the ion exchange treatment is 0.5-14 hours, preferably 4-10 hours.
[0076] As can be seen from the above, according to the chemically strengthened microcrystalline glass and its preparation method provided by the scheme of the present application, the chemically strengthened microcrystalline glass includes two Boltzmann distributed crystal layers of preset thickness extending inward from two outer surfaces respectively, and a uniformly distributed crystal layer located between the two Boltzmann distributed crystal layers, and the thickness of each Boltzmann distributed crystal layer is greater than 0 and less than or equal to 200 μm; the crystal ratio of each Boltzmann distributed crystal layer gradually increases from the outer surface to the inner part of the chemically strengthened microcrystalline glass, and the maximum crystal ratio of the Boltzmann distributed crystal layer is 50% to 89%, and the minimum crystal ratio is 30% to 65%.
[0077] The beneficial effects include at least the following aspects:
[0078] 1. In conventional glass-ceramics, heterogeneous phases such as crystals are directly coupled with the glass phase, often leading to defects such as stress concentration, microcracks, and delamination. However, the functionalized composite microcrystalline materials with a Boltzmann gradient distribution of crystal phases provided in the embodiments of this application can reduce such defects by gradually transitioning from one material to another.
[0079] 2. The embodiments of the present application improve the fracture properties (i.e., fracture toughness, tensile strength, etc.) of the microcrystalline glass through a crystal phase-glass phase gradient distribution, especially a Boltzmann gradient distribution of the crystal phase. In addition, in the functional gradient material with a crystal phase-glass phase Boltzmann distribution, the gradual change in Young's modulus due to stress redistribution can prevent the formation of Hertz cone cracks, and the sliding contact resistance can also be optimized. In particular, the microcrystalline glass formed based on the Li2O-Al2O3-SiO2 base glass in the embodiments of the present application exhibits a higher Young's modulus and fracture toughness.
[0080] 3. According to Griffith's criterion, cracks will propagate if the total surface energy required to create a new surface can be provided by the elastic deformation energy stored in the body. When thin glass is subjected to external impact, the crack preferentially moves within the entire glass phase because the mechanical strength of the glass phase is weaker than that of the crystalline phase. Based on this, the embodiments of the present application follow a tortuous path, rationally designing the proportion of the glass phase to provide greater compressive stress to offset external tensile stress, preventing the glass from creating new surfaces and effectively preventing glass breakage.
[0081] 4. In order to create crystals that follow the Boltzmann distribution in microcrystalline glass, the present invention provides a method for obtaining compressive stress by forming a Boltzmann crystal distribution and ion exchange (IOX). This is achieved by using IOX for a certain period of time within a suitable temperature and viscosity range. By giving a suitable temperature and viscosity, some crystals can participate in IOX, which in turn causes the crystal structure to be destroyed, and after a sufficiently long time, these "destroyed crystals" re-form a complete structure with the glass phase. This avoids the inability to achieve a gradient distribution of the Boltzmann distribution due to too high a temperature, too low a viscosity, or too many crystals disappearing, thereby effectively achieving a gradual change in mechanics and bringing about an improvement in strength.
[0082] The chemically strengthened glass-ceramics in this application, due to the above structure, ensures the uniformity of stress distribution on the glass surface, effectively avoids glass edge warping, reduces stress relaxation, and improves the mechanical properties of the glass. Specifically, as the crystal content changes, the stress distribution on the glass surface will also change accordingly. When the trend of the crystal content change is a uniform and gradual increase from the outer surface to the inner part of the chemically strengthened glass-ceramics, the stress distribution on the glass surface also changes uniformly. The uniform stress change makes the glass-ceramics more resistant to impact forces, and can effectively avoid glass edge warping and reduce stress relaxation, so that the entire glass has better mechanical properties.
[0083] It should be understood that the content described in this section is not intended to identify the key or important features of the present application, nor is it intended to limit the scope of the present application. The further effects of the above non-conventional optional manner will be described below in conjunction with specific embodiments. DETAILED DESCRIPTION
[0084] To make the purpose, features, and advantages of the invention of this application more obvious and easy to understand, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the embodiments described are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without making creative efforts shall fall within the scope of protection of this application.
[0085] In the description of the embodiments of the present application, the term "multiple" means two or more, unless otherwise clearly and specifically limited; the term "including" indicates the presence of the described features, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections; the term "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may include the existence of A alone, the existence of A and B at the same time, and the existence of B alone. The character " / " generally indicates that the related objects before and after are in an "or" relationship; the term "about" means that the content, size, parameter, etc. are not and do not need to be exact. If necessary, they can be approximate or higher or lower. Generally speaking, regardless of whether there is an explicit description, the content, size, parameter, etc. should be "about" or "approximate"; the terms "preferably" and "optional" are not used to limit the scope of the present application, nor do they mean that certain technical features are critical or indispensable to the implementation methods of the present application. Instead, they should be understood as merely indicating specific aspects of the embodiments of the present application.
[0086] First, the relevant terms involved in the embodiments of the present application are explained here and the relevant detection methods are described as follows:
[0087] Crystalline content testing: Importing XRD test results (RAW format) into the X-ray diffraction data Rietveld refinement software JADE Standard 8.6 for fitting and analysis can determine the crystalline phase in the glass-ceramic sample. Crystalline content, as used herein, refers to the percentage (i.e., weight percentage) of crystals or crystalline phases in the mass of the glass-ceramic.
[0088] Determination of Crystalline Content: Import XRD test results (RAW format) into the X-ray diffraction data Rietveld refinement software JADE Standard 8.6 for fitting and calculation to determine the crystal content of the glass-ceramic sample. Specifically, the ratio of the fitted crystalline phase peak area to the total fitted peak area is the crystal content.
[0089] Average crystal size test: The average crystal size of the sample can be calculated using the result data obtained from the XRD test according to the Scherrer formula D = Kλ / (βcosθ). Wherein, λ is the X-ray wavelength, λ = 0.154056nm, β is the half-height width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW file (diffraction pattern) output by the XRD instrument is curve fitted in JADE Standard 8.6 software. Jade outputs a fitting report. According to the angle 2θ value and Peak FWHM value (half-height width of the diffraction peak) corresponding to each diffraction peak in the fitting report, the Peak FWHM value is converted to radians: β = (FWHM / 180×3.14). The grain size of each diffraction peak is calculated by the Scherrer formula D = Kλ / (βcosθ) and then averaged to obtain the average crystal size.
[0090] When glass undergoes chemical strengthening (ion exchange), a compressive stress layer forms on the surface, balanced by tensile stress within the glass. This stress distribution causes the glass to exhibit refractive index anisotropy (birefringence): different stress directions result in different refractive indices, causing phase delay in the light passing through it.
[0091] FSM test principle:
[0092] FSM measures the phase delay caused by stress to infer the stress magnitude. The specific steps are as follows:
[0093] (1) Polarized light interference
[0094] Light source: Monochromatic light (such as laser) is converted into linearly polarized light through a polarizer.
[0095] Sample effect: When light passes through glass, the birefringence effect of the stress area decomposes the light into two beams of orthogonal polarization (fast axis and slow axis), resulting in a phase difference (δ).
[0096] Polarizer analysis: After passing through the polarizer, the two beams of light interfere with each other, forming alternating light and dark stripes (a stripe pattern).
[0097] (2) Relationship between stripes and stress
[0098] The phase difference δ is proportional to the stress (σ) and the sample thickness (d):
[0099]
[0100] Where C is the stress-optical coefficient and λ is the wavelength of light.
[0101] Fringe spacing: The phase difference between adjacent fringes is 2π. The local stress gradient can be calculated by measuring the fringe spacing.
[0102] (3) Surface stress calculation
[0103] The surface compressive stress (CS) and the depth of the stress layer (DOL) are derived from the fringe distribution using models such as the semi-infinite plate model.
[0104] Glass-ceramics, also known as glass-ceramics, are a type of solid composite material consisting of both a glass phase and a microcrystalline phase, produced by targeted, controlled heat treatment of a precursor glass. The microcrystalline phase can also be referred to as the crystalline phase, crystal phase, or crystalline phase.
[0105] Chemically strengthened glass-ceramics refers to the solid composite material obtained by chemically strengthening glass-ceramics (also known as ion exchange). It should be understood that during high-temperature chemical strengthening or ion exchange, alkali metal ions with large ionic radii (such as potassium and sodium ions) in the salt bath (also known as molten salt) replace alkali metal ions with smaller ionic radii (such as sodium and lithium ions) in the glass-ceramics. This creates a volume difference between the exchanged ions and produces compressive stresses from high to low on the surface of the glass-ceramics, hindering and delaying the expansion of microcracks and thus improving the mechanical strength of the glass-ceramics.
[0106] Nucleation temperature: refers to the temperature at which crystal nuclei are formed.
[0107] Crystallization temperature: refers to the temperature at which the target crystal growth rate can be controlled.
[0108] Transmittance: When light of a certain wavelength hits the glass surface, the light will be reflected, absorbed and transmitted. The ratio of the intensity of the transmitted part to the intensity of the incident light is the transmittance.
[0109] In the examples of this application, the average transmittance of the glass-ceramics in the visible light range refers to the average transmittance of the glass-ceramics measured at wavelengths between 360 nm and 740 nm. The examples of this application use a Konica Minolta CM-3600A spectrophotometer to measure the average transmittance of the glass-ceramics at wavelengths between 360 nm and 740 nm.
[0110] Crystallinity: refers to the percentage of the total mass of the crystalline phase / crystals in the microcrystalline glass to the mass of the microcrystalline glass.
[0111] Haze (C) refers to the percentage of the transmitted light intensity that deviates from the incident light by more than 2.5° to the total transmitted light intensity. The haze values in the examples of this application are measured using a Konica Minolta CM-3600A spectrophotometer under standard C light source.
[0112] In the embodiments of the present application, CS_50 refers to the compressive stress value at a depth of 50 μm from the glass surface.
[0113] In the embodiment of the present application, |CT_CV| refers to the absolute value of the maximum value of the tensile stress, specifically refers to the absolute value of the maximum value of all tensile stresses in the tensile stress layer.
[0114] In the embodiments of the present application, |CT_AV| refers to the absolute value of the average tensile stress in the tensile stress layer, specifically refers to the absolute value of the average value of all tensile stresses in the tensile stress layer.
[0115] In the embodiment of the present application, DOL_0 refers to the depth of the compressive stress layer, also known as the depth of the compressive stress layer, which refers to the distance from any surface of the glass to a position close to the surface where the compressive stress is zero.
[0116] In a first aspect, in order to make the strengthened micro-ceramics have excellent drop resistance, the embodiments of the present application provide strengthened micro-ceramics with the following crystallization characteristics and stress characteristics.
[0117] Typical drop impacts are puncture-type failures. Sharp particles can easily penetrate the glass surface CS, creating a 30-50 micron deep pit. Cracks then form at this pit, extending through the compressive stress zone and shattering the glass. CS_50 represents the compressive stress at a depth of 50 microns. A higher stress at this point inhibits crack formation at the pit, while a deeper DOL-0 indicates a larger crack propagation barrier. CT-CV represents the point of maximum tensile stress, similar to the average tensile stress value of CT-AV. It indirectly indicates the magnitude of deep compressive stress. Better stress performance indicates less crack propagation.
[0118] Drop test: A glass piece is attached to a 200g counterweight steel sheet to simulate the entire device falling.
[0119] The substrate glass was heat treated in a resistance furnace. Following heat treatment procedures (nucleation temperature / nucleation time, crystallization temperature / nucleation time, and heating rate during the heat treatment process), chemically strengthened glass-ceramics were obtained. The glass-ceramics were then cut, CNC machined (using a computer numerical control machine, RCG500S), and polished to obtain the mirror-smooth glass-ceramics sheets.
[0120] The physical properties of the prepared glass-ceramics were tested according to the following method:
[0121] Upper and lower limits of crystallization: Use an Orton GTF-MD-16 gradient furnace for testing. Place the glass strip on the ceramic tube of the Orton gradient furnace, set the heating parameters, and after the furnace cools down, remove the sample and record the corresponding position. Since the temperature at one end of the sample is low and the other end is high, the temperature can be accurately determined. Refer to the standard ASTM E 228-17.
[0122] Vickers Hardness Test: A diamond Vickers indenter is pressed into the specimen surface with a load ranging from 1.916N to 49.03N to form an indentation. The load is divided by the surface area of the indentation, calculated from the average diagonal length of the indentation. Refer to standard GBT37900-2019.
[0123] Fracture toughness test: A diamond Vickers indenter is pressed into the specimen surface with a load ranging from 1.916N to 49.03N to form an indentation. Pre-cracks are generated at the four vertices of the indentation. The value is calculated based on the load and the indentation crack propagation length, referring to the standard GBT 37900-2019.
[0124] Young's modulus test: The Young's modulus of the sample was obtained by ultrasonic testing using the UMS-100 ultrasonic material characterization system, with reference to the standard GBT 37780-2019.
[0125] XRD testing: The glass-ceramics were ground into a fine glass powder with a particle size of less than 75 μm using a mill. The powder was then tested using an X-ray diffractometer (Shimadzu XRD-6100) to obtain an XRD diffraction peak curve. The X-ray diffractometer used in the present invention was a Shimadzu XRD-6100, with a copper target, an incident angle range of 2θ = 10-80°, a scan speed of 0.2° / min, an operating voltage of 40 kV, and an operating current of 30 mA. The XRD diffraction data were then analyzed using JADE software to determine the crystalline phase of the sample.
[0126] Average grain size: The average grain size of the sample can be calculated using the result data obtained from the XRD test according to the Scherrer formula D = Kλ / (βcosθ), where λ is the X-ray wavelength, λ is 0.154056nm, β is the half-maximum width of the diffraction peak, and θ is the Bragg diffraction angle. Specifically, the RAW file (diffraction pattern) output by the XRD instrument is curve fitted in the Jade software, and Jade outputs a fitting report. According to the angle 2θ value and Peak FWHM value (half-maximum width of the diffraction peak) corresponding to each diffraction peak in the fitting report, the Peak FWHM value is converted to radians β = (FWHM / 180*3.14), and the grain size of each diffraction peak is calculated by D = Kλ / (βcosθ) and then averaged to obtain the average grain size. Testing method for crystal content / crystallinity: Import the X-ray diffractometer test result file (RAW format) into the X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, Maud, Topas), perform fitting and calculation, and then obtain the crystal content / crystallinity in the microcrystalline glass sample. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content, which is also referred to as crystallinity in the present invention.
[0127] b value determination: The b value was obtained by testing the sample using a Konica Minolta spectrophotometer CM-3600A from Japan, and the average value of 5 parallel samples was taken as the b value result of the sample to be tested.
[0128] Transmittance was measured according to the standard "GB / T 7962.12-2010 Test Methods for Colorless Optical Glass - Part 12: Spectral Transmittance." The glass-ceramic sample was first cleaned in an ultrasonic cleaner using the following cleaning conditions: 5-10 minutes; detergent: a 10-fold dilution of standard dishwashing liquid; temperature: 45°C-65°C; frequency: 20kHz-40kHz. The transmittance was then measured using a haze meter (Konica Minolta CM-3600A Spectrophotometer, Japan) at different wavelengths.
[0129] The transmittance of the sample under 550nm wavelength light was measured using a Konica Minolta spectrophotometer CM-3600A from Japan, and the average value of 5 parallel samples was taken as the transmittance result of the sample to be tested under 550nm wavelength light.
[0130] Glass thickness: Determined by micrometer testing. It should be understood that the degree of ion exchange varies gradually from the surface to the center of the glass through the thickness. The total Na-K and / or Li-Na exchange typically does not exceed 1% of the sample's mass, and the difference in ion radius is typically on the order of micrometers. Therefore, the expansion effect through the thickness is minimal, and the thickness can be considered essentially unchanged. In other words, the change in thickness of the glass-ceramic before and after chemical strengthening is negligible and very small.
[0131] Density determination: The density of the glass-ceramic sample was tested according to the principle of “Archimedes drainage method”. The testing instrument used in the present invention was an ALFA MIRAGE electronic density balance SD-200.
[0132] In conventional glass-ceramics, heterogeneous phases such as crystals are directly coupled to the glass phase, often leading to defects such as stress concentration, microcracks, and delamination. However, the functionalized composite microcrystalline materials provided in the embodiments of the present application, in which the crystal phases are distributed in a Boltzmann gradient, can reduce such defects by gradually transitioning from one material to another.
[0133] The embodiments of the present application improve the fracture properties of glass-ceramics through a crystal-glass phase gradient distribution, particularly a Boltzmann gradient distribution of the crystal phase. The applicant has discovered through research that in functionally gradient materials with a crystal-glass phase Boltzmann distribution, the gradual change in Young's modulus due to stress redistribution can prevent the formation of Hertz cone cracks and optimize sliding contact resistance. In particular, the glass-ceramics formed from the Li2O-Al2O3-SiO2 base glass in the embodiments of the present application exhibit excellent mechanical properties, such as higher Young's modulus and fracture toughness.
[0134] According to Griffith's criterion, cracks will propagate if the total surface energy required to create a new surface can be provided by the elastic deformation energy stored in the body. When thin glass is subjected to external impact, because the mechanical strength of the glass phase is weaker than that of the crystalline phase, the crack preferentially moves throughout the glass phase. Based on this, the embodiments of the present application follow a tortuous path, and the rational design of the proportion of the glass phase can provide greater compressive stress to offset the external tensile stress, so that the glass avoids creating a new surface, which effectively prevents the glass from breaking.
[0135] In order to create crystals that follow the Boltzmann distribution in microcrystalline glass, an embodiment of the present application provides a method for obtaining compressive stress by forming a Boltzmann crystal distribution and ion exchange (IOX). Below the glass transition temperature (Tg), the viscosity of the glass is very high, and it is difficult to change the distribution of existing crystals. Therefore, it is necessary to achieve this through IOX for a certain period of time within a suitable temperature viscosity range. Under suitable temperature viscosity, some crystals can participate in IOX, causing the crystal structure to be destroyed, and through a sufficiently long time, these "destroyed crystals" re-form a complete structure with the glass phase. If the temperature is too high, the viscosity is too low, or there are too many crystals that disappear, the Boltzmann distribution gradient distribution cannot be achieved, thereby effectively achieving a gradual change in mechanics and bringing about an increase in strength.
[0136] Unless otherwise indicated in specific circumstances, the numerical ranges described in the examples of the present application are intended to include the endpoints of the numerical range and all integers and fractions within the range. When an amount, solubility or other parameter is described in the form of a preferred range or preferred value, it should be understood that it is equivalent to revealing any range by combining any preferred range with a preferred range, a preferred value with a preferred value, or a preferred range with a preferred value, without considering whether such pairwise combinations are specifically explained in the examples.
[0137] Unless otherwise specified in specific circumstances, the component contents described in the examples of the present application are expressed in molar percentage (mol%).
[0138] To at least partially address the problems of uneven surface stress distribution, prone edge warping, and stress relaxation in glass-ceramics provided in related arts, resulting in poor mechanical properties, one embodiment of the present application provides a chemically strengthened glass-ceramic comprising two Boltzmann distributed crystal layers extending inward from two outer surfaces to a predetermined thickness, and a uniformly distributed crystal layer located between the two Boltzmann distributed crystal layers. The thickness of each Boltzmann distributed crystal layer is greater than 0 and less than or equal to 200 μm. The crystal ratio of each Boltzmann distributed crystal layer gradually increases from the outer surface to the interior of the chemically strengthened glass-ceramic, with a maximum crystal ratio of 50% to 89% and a minimum crystal ratio of 30% to 65%. A Boltzmann distributed crystal layer refers to a layer in which the rate of crystal increase satisfies the Boltzmann distribution, i.e., the average crystal content per unit thickness in the thickness direction of the glass-ceramic is fitted to a function graph that conforms to the Boltzmann function.
[0139] The chemically strengthened glass described in this application undergoes a chemical strengthening process in which smaller ions (usually sodium ions) in the glass's surface layer are replaced by larger ions (usually potassium ions). Because larger ions occupy more space, this exchange creates compressive stress on the glass's surface, thereby enhancing its mechanical properties. Furthermore, this ion exchange affects the crystal content of the glass-ceramic due to decrystallization of the crystals in the glass-ceramic during the high-temperature salt bath process.
[0140] The thickness of the chemically strengthened glass-ceramics of this embodiment is greater than 350 to 700 μm, with a preferred thickness of 500 μm. The chemically strengthened glass-ceramics has a composite structure, with a first Boltzmann distributed crystal layer, a uniformly distributed crystal layer, and a second Boltzmann distributed crystal layer from one outer surface to the other. For any Boltzmann distributed crystal layer, the crystal ratio at the position corresponding to the outer surface of the glass is the smallest, and the crystal ratio at the position adjacent to the uniformly distributed crystal layer is the largest, that is, the crystal ratio of the Boltzmann distributed crystal layer gradually increases from the surface to the inner layer. For the uniformly distributed crystal layer, the crystal ratio at different depths is uniformly distributed, that is, the crystal ratio of the uniformly distributed crystal layer is equal to the maximum crystal ratio of the Boltzmann distributed crystal layer.
[0141] The thickness of the Boltzmann distribution crystal layer of this embodiment can preferably be 100-200μm, for example, 100μm, 105μm, 110μm, 115μm, 120μm, 125μm, 130μm, 135μm, 140μm, 145μm, 150μm, 155μm, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm, and 200μm.
[0142] It is worth mentioning that at least a portion of the Boltzmann distribution crystal layer of this embodiment has compressive stress, which is greater than 50 and less than or equal to 270 MPa. In a preferred embodiment of this embodiment, the ratio of the compressive stress to the depth of the compressive stress layer is greater than or equal to 7.5.
[0143] In an optional implementation manner of this embodiment, the measurement tolerance of the crystal ratio of the uniformly distributed crystal layer of this embodiment is ±5%; in addition, the uniformly distributed crystal layer of this embodiment has tensile stress, and its tensile stress line density CTLD is greater than or equal to 26000 MPa, preferably can be 26000~34000 MPa, for example, 26000 MPa, 26500 MPa, 27000 MPa, 27500 MPa, 28000 MPa, 28500 MPa, 29000 MPa, 29500 MPa, 30000 MPa, 30500 MPa, 31000 MPa, 31500 MPa, 32000 MPa, 32500 MPa, 33000 MPa, 33500 MPa, 34000 MPa.
[0144] It's important to note that tensile stress linear density (CTLD) is used to measure the strength and safety of glass. Generally speaking, CTLD is defined as the average value of the total tensile stress within the glass along its thickness. It can be thought of as the compressive stress per unit thickness of the glass, after the surface compressive stress is evenly distributed throughout the entire thickness. CTLD not only reflects the average effect of surface compressive stress on the entire cross-section, but also, under conditions of static equilibrium, requires that surface compressive stress and internal tensile stress remain in overall mechanical equilibrium. Therefore, by integrating the compressive stress along the thickness and amortizing it over the total thickness, CTLD can be used to assess the distribution of internal stress within the glass. If ultra-thin IOX glass is considered a two-dimensional, infinitely large flat sheet of glass, with negligible stress along the thickness, its volumetric stress level approximates CTLD. Quantitative calculation of CTLD more accurately reflects the glass's overall resistance to damage when subjected to large external forces and high-speed strains, such as drop impacts, and this metric is directly proportional to the integral of the compressive stress. Therefore, CTLD also represents the stress level stored in glass after IOX. A higher CTLD means greater energy storage, which, while increasing strength, may also increase the risk of delayed failure or spontaneous explosion under environmental stress. In summary, CTLD is not only an important parameter for evaluating glass strength but also a key indicator that cannot be ignored in safety design.
[0145] Based on the above description, the CTLD calculation formula can be expressed as:
[0146]
[0147] Wherein, CTLD is the tensile stress linear density, in MPa; CT(t) is the tensile stress corresponding to different positions in the thickness direction, in MPa; t is the glass thickness, in mm.
[0148] Since the total amount of tensile stress and compressive stress is conserved, the above CTLD calculation formula can also be expressed as:
[0149]
[0150] Where CTLD is the tensile stress linear density, in MPa; CS(t) is the compressive stress corresponding to different positions in the thickness direction, in MPa; t is the glass thickness, in mm.
[0151] For IOX LAS glass, the measurement of tensile stress is more accurate, and the above CTLD calculation formula can be expressed as:
[0152]
[0153] Wherein, CTLD is the tensile stress linear density, in MPa; CT_AV is the average tensile stress, in MPa; DOL_0 is the maximum depth of compressive stress, in μm; t is the glass thickness, in mm.
[0154] In the present application, since the glass is immersed in a molten alkali metal salt bath, and the larger diameter alkali metal ions K+ or Na+ in the salt bath undergo ion exchange with the smaller diameter alkali metal ions Na+ or Li+ in the glass, the "pinching effect" produced by the ion exchange forms a large compressive stress on the glass surface. Simply put, the stress is caused by the volume difference before and after the exchange.
[0155] Since chemically strengthened glass has compressive stress, tensile stress will be generated inside the glass according to the principles of mechanics. The total integral of the surface compressive stress is conserved and equal to the total integral of the internal tensile stress. Therefore, the average value of the central tensile stress integral over the thickness of the glass cover is the central tensile stress line density, or CTLD.
[0156] So CTLD=CT-IN / T
[0157] Where: CT-IN is the total CT integral, T is the glass thickness
[0158] During ion exchange, stress increases due to the "pinching effect." However, during salt bath exchange, atoms / ions in the glass network undergo local rearrangement over time, partially releasing stress. K+ diffuses inward or Na+ migrates in the opposite direction, reducing the concentration gradient and causing stress attenuation. At high temperatures, glass exhibits viscoelasticity, and stress is relaxed through microscopic flow. The stress reduction caused by relaxation is expressed as follows:
[0159] It is worth mentioning that the chemically strengthened microcrystalline glass of this embodiment is obtained by ion exchange treatment based on microcrystalline glass of preset components, and the components of the microcrystalline glass, in molar percentage, include: SiO2 greater than or equal to 60% and less than or equal to 78%; Al2O3 greater than or equal to 1.5% and less than or equal to 6.7%; Li2O greater than or equal to 16% and less than or equal to 26.8%; P2O5 greater than or equal to 0.1 and less than or equal to 2.5%; ZrO2 greater than or equal to 0 and less than or equal to 5%; RO greater than or equal to 0 and less than or equal to 5.3%, and RO includes at least one of CaO, MgO, ZnO, and BaO; Na2O greater than or equal to 0% and less than or equal to 6.5%; K2O greater than or equal to 0 and less than or equal to 4%; and clarifier greater than or equal to 0 and less than or equal to 1%.
[0160] SiO2 is a basic component of the glass composition provided in this application. It is a network structure former of glass and glass-ceramics and can form lithium silicate and lithium disilicate after crystallization. It should be noted that if the SiO2 content is low, the crystals formed in the glass-ceramics will be fewer and the crystals will be more coarse, affecting the haze and drop ball test height of the glass-ceramics and glass-ceramics products. Therefore, the lower limit of the SiO2 content is set at 60%. In addition, if the SiO2 content is higher than a certain level, the glass melting temperature will be high, the material will be difficult to form, and it will not be easy to form, affecting the consistency of the glass. Therefore, the upper limit of the SiO2 content is set at 78%. In some embodiments, the glass composition may contain about 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, or 78% SiO2. In some embodiments, the glass composition may further include SiO2 in an amount such as greater than or equal to 61% and less than or equal to 77%, greater than or equal to 62% and less than or equal to 76%, greater than or equal to 63% and less than or equal to 75%, greater than or equal to 64% and less than or equal to 74%, greater than or equal to 65% and less than or equal to 73%, greater than or equal to 66% and less than or equal to 72%, greater than or equal to 50% and less than or equal to 71%, or greater than or equal to 68% and less than or equal to 70%.
[0161] Al2O3 can be a component that forms the glass network structure or a cationic network member that acts as a charge balancer. In this application, Al2O3 is fully incorporated into the glass network structure, increasing the depth of the ion exchange layer and the surface compressive stress of the glass-ceramic product, enhancing the chemical stability of the glass, and improving its mechanical properties. On the one hand, if its content is below a certain level, it will result in poor results. Therefore, the lower limit of the Al2O3 content by mass is 1.5%. On the other hand, if the Al2O3 content is above a certain level, the glass's meltability and devitrification resistance will be reduced, and the crystals will tend to grow larger during crystallization, reducing the strength of the glass-ceramic and glass-ceramic products. Therefore, the upper limit of the Al2O3 content is 6.7%. In some embodiments, the glass composition may contain approximately 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, or 6.7% Al2O3. In some embodiments, the glass composition may further include Al2O3 in an amount such as greater than or equal to 2% and less than or equal to 6.5%, greater than or equal to 2.5% and less than or equal to 6%, greater than or equal to 3% and less than or equal to 5.5%, greater than or equal to 3.5% and less than or equal to 5%, or greater than or equal to 4% and less than or equal to 4.5%.
[0162] Li2O is an essential component that forms a crystalline phase upon crystallization, contributing to the formation of lithium-containing crystalline phases such as lithium disilicate, petalite, and lithium silicate. It is also essential for chemical strengthening. However, if its content falls below a certain level, the effect is poor. Therefore, the lower limit of the Li2O content is 16%. Furthermore, if its content exceeds a certain level, the chemical stability of the glass is negatively impacted. Therefore, the upper limit of the Li2O content is preferably 26.8%. In some embodiments, the glass composition may include approximately 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, or 26.8% Li2O. In some embodiments, the glass composition may further include Li2O in an amount such as greater than or equal to 16.5% and less than or equal to 26.5%, greater than or equal to 17% and less than or equal to 26%, greater than or equal to 17.5% and less than or equal to 25.5%, greater than or equal to 18% and less than or equal to 25%, greater than or equal to 18.5% and less than or equal to 24.5%, greater than or equal to 19% and less than or equal to 24%, greater than or equal to 19.5% and less than or equal to 23.5%, greater than or equal to 20% and less than or equal to 23%, greater than or equal to 20.5% and less than or equal to 22.5%, or greater than or equal to 21% and less than or equal to 22%.
[0163] P2O5 helps improve the low-temperature melting properties of glass, enables phase separation and formation of crystal nuclei within the glass, and improves the thermal expansion stability of the glass during the crystallization process. The lower limit of the P2O5 content can be 0.1%. However, excessive P2O5 can easily reduce the glass's resistance to devitrification, cause phase separation, and deteriorate the glass's mechanical properties. Therefore, the upper limit of the P2O5 content is 2.5%. In some embodiments, the glass composition may include approximately 0.1%, 0.5%, 1%, 1.5%, 2%, or 2.5% P2O5. In some embodiments, the glass composition may also include P2O5 in amounts such as greater than or equal to 0.5% and less than or equal to 2%, or greater than or equal to 1% and less than or equal to 1.5%.
[0164] ZrO2 acts as a nucleating agent and helps improve the chemical stability of the glass. In this embodiment, the lower limit of the ZrO2 content can be 0. However, if too much ZrO2 is contained, the glass's resistance to devitrification is easily reduced, and the control of the glass crystallization process becomes more difficult. Therefore, the upper limit of the ZrO2 content is 5%. In some embodiments, the glass composition may include approximately 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5% ZrO2. In some embodiments, the glass composition may also include ZrO2 in amounts such as greater than or equal to 0.5% and less than or equal to 4.5%, greater than or equal to 1% and less than or equal to 4%, greater than or equal to 1.5% and less than or equal to 3.5%, or greater than or equal to 2% and less than or equal to 3%.
[0165] Na2O helps lower the glass transition temperature and crystallization temperature and inhibits the precipitation of unintended impurities. Its lower limit can be 0. However, if the Na2O content is too high, it increases the thermal expansion coefficient of the glass and reduces its thermal stability. Therefore, its upper limit is set at 6.5%. In some embodiments, the glass composition may include approximately 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, or 6.5% Na2O. In some embodiments, the glass composition may also include Na2O in amounts such as greater than or equal to 0.5% and less than or equal to 6%, greater than or equal to 1% and less than or equal to 5.5%, greater than or equal to 1.5% and less than or equal to 5%, greater than or equal to 2% and less than or equal to 4.5%, greater than or equal to 2.5% and less than or equal to 4%, or greater than or equal to 3% and less than or equal to 3.5%.
[0166] This embodiment optionally introduces 0-4% molar percentage of K2O into the glass composition, for example, 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, and 4% K2O. In some embodiments, the glass composition may further include K2O in amounts such as: greater than or equal to 0.5% and less than or equal to 4%, greater than or equal to 1% and less than or equal to 3.5%, greater than or equal to 1.5% and less than or equal to 3%, and greater than or equal to 2% and less than or equal to 2.5%. It is worth noting that the presence of multiple alkali metal oxides in the glass composition can exert a mixed alkali effect during the chemical strengthening of the glass-ceramics, restricting the migration of alkali metal ions during ion diffusion and helping to improve the chemical stability of the glass. Furthermore, the interaction of multiple alkali metal oxides can enhance the low-temperature melting and formability of the glass, and has a certain effect on lowering the softening point and molding temperature of the glass, thereby reducing the difficulty of chemical strengthening the glass-ceramics.
[0167] RO is an alkaline earth metal oxide, including at least one of CaO, MgO, ZnO, and BaO. The lower limit of the alkaline earth metal oxide content is 0 and the upper limit is 5.3%. In some embodiments, the glass composition may include approximately 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or 5.3% of the alkaline earth metal oxide. In some embodiments, the glass composition may also include alkaline earth metal oxide in an amount such as greater than or equal to 0.5% and less than or equal to 5%, greater than or equal to 1% and less than or equal to 4.5%, greater than or equal to 1.5% and less than or equal to 4%, greater than or equal to 2% and less than or equal to 3.5%, or greater than or equal to 2.5% and less than or equal to 3%.
[0168] In an optional embodiment of this embodiment, the glass composition includes: CaO (0% to 4%), MgO (0% to 4%), ZnO (0% to 4%), and BaO (0% to 4%). CaO helps reduce the high-temperature viscosity of the glass and increases its density; MgO helps reduce the viscosity of the glass, inhibits crystallization during glass forming, and improves its low-temperature melting properties; ZnO improves the melting properties of the glass, enhances its chemical stability, and refines the grain size during crystallization; and BaO improves the glass's glass-forming properties.
[0169] The glass composition of this embodiment may further include a fining agent, comprising one or more of SnO2, Sb2O3, and CeO2. The lower limit of the fining agent content is 0% and the upper limit is 1%. In some embodiments, the glass composition may include approximately 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1% of the fining agent. In some embodiments, the glass composition may further include a fining agent in an amount such as greater than or equal to 0.1% and less than or equal to 0.9%, greater than or equal to 0.2% and less than or equal to 0.8%, greater than or equal to 0.3% and less than or equal to 0.7%, or greater than or equal to 0.4% and less than or equal to 0.6%.
[0170] In an optional implementation manner of this embodiment, the components of the microcrystalline glass, expressed in molar percentage, further include: B2O3 greater than or equal to 0 and less than or equal to 4.8%; and / or, TiO2 greater than or equal to 0% and less than or equal to 4%; and / or, Y2O3 greater than or equal to 0 and less than or equal to 4%; and / or, La2O3 greater than or equal to 0 and less than or equal to 0.5%.
[0171] B2O3 can lower the melting temperature of glass and remain in the glass phase after crystallization, ensuring the structural stability of the glass phase and improving the chemical stability of microcrystalline glass. However, too much B2O3 will increase volatilization during the glass melting process and increase the difficulty of glass homogenization. Based on this, the upper limit of the B2O3 content is set at 4.8%. In some embodiments, the glass composition may contain approximately 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 4.8% B2O3. In some embodiments, the glass composition may also contain B2O3 in amounts such as: greater than or equal to 0.5% and less than or equal to 4.8%, greater than or equal to 1% and less than or equal to 4.5%, greater than or equal to 1.5% and less than or equal to 4%, greater than or equal to 2% and less than or equal to 3.5%, and greater than or equal to 2.5% and less than or equal to 3%.
[0172] TiO2 helps lower the melting temperature of glass and improve its chemical stability. By introducing less than 4% by mass of TiO2, the glass crystallization process can be easily controlled. This embodiment optionally includes approximately 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, or 4% TiO2. In some embodiments, the glass composition may further include TiO2 in amounts such as greater than or equal to 0.5% and less than or equal to 3.5%, greater than or equal to 1% and less than or equal to 3%, or greater than or equal to 1.5% and less than or equal to 2.5%.
[0173] An appropriate amount of Y2O3 can increase the density of the glass phase and enhance the overall strength of the glass-ceramics. However, if the Y2O3 content is too high, it will be difficult to obtain a large compressive stress value during the chemical strengthening treatment of the glass-ceramics. This embodiment optionally includes approximately 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, and 4% Y2O3. In some embodiments, the glass composition may also include Y2O3 in amounts such as greater than or equal to 0.5% and less than or equal to 3.5%, greater than or equal to 1% and less than or equal to 3%, and greater than or equal to 1.5% and less than or equal to 2.5%.
[0174] In an optional implementation of this embodiment, the components of the microcrystalline glass before ion exchange include, in molar percentage, the following: SiO2 greater than or equal to 60% and less than or equal to 78%; Al2O3 greater than or equal to 2% and less than or equal to 6.7%; Li2O greater than or equal to 16% and less than or equal to 24%; P2O5 greater than or equal to 0.1% and less than or equal to 2.2%; ZrO2 greater than or equal to 0 and less than or equal to 5%; RO greater than or equal to 0 and less than or equal to 5.3%, and RO includes at least one of CaO, MgO, ZnO, and BaO; Na2O greater than or equal to 0% and less than or equal to 5%; K2O greater than or equal to 0 and less than or equal to 4%; and clarifier greater than or equal to 0 and less than or equal to 1%.
[0175] In an optional implementation manner of this embodiment, the crystalline phase of the chemically strengthened microcrystalline glass includes one or more of lithium disilicate, petalite, quartz and quartz solid solution, spodumene, lithium metasilicate, sodium nepheline, spinel, wollastonite, cordierite, etc.
[0176] In one embodiment, the crystalline phase of the chemically strengthened microcrystalline glass mainly includes lithium disilicate and petalite, with lithium metasilicate and spodumene existing in trace amounts as impurity phases; in another embodiment, the crystalline phase of the chemically strengthened microcrystalline glass is lithium disilicate, with lithium metasilicate and spodumene existing in trace amounts as impurity phases.
[0177] In an optional implementation manner of this embodiment, the chemically strengthened glass-ceramics satisfies the following crystal content relationship:
[0178] F(x)=W*(-a / a*(T*t) / (1+exp((x i -x0) / (dx)))
[0179] Wherein, F(x) represents the crystal ratio of chemically strengthened glass-ceramics at depth x, W represents the crystal content of chemically strengthened glass-ceramics before strengthening, a is a constant, T represents the temperature of the chemical strengthening salt bath, t represents the duration of ion exchange treatment, and x i represents the depth from the glass surface to i, x0 represents the depth of the glass surface; and, 20%<F(x)<75%, 30% <W<75%,0<a<0.001,0<x i <250μm.
[0180] In an optional implementation manner of this embodiment, the value of the above-mentioned F(x) can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%, and its value range can preferably be 25% to 70%, 30% to 65%, 35% to 60%, 40% to 55%, or 45% to 50%.
[0181] In an optional implementation manner of this embodiment, the value of the above-mentioned W can be 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%, and its value range can preferably be 35% to 70%, 40% to 65%, 45% to 60%, or 50% to 55%.
[0182] In an optional implementation manner of this embodiment, the value of a can be 0.0001, 0.0002, 0.0003, 0.0004, 0.0005, 0.0006, 0.0007, 0.0008, or 0.0009, and its value range can preferably be 0.0001 to 0.0009, 0.0002 to 0.0008, 0.0003 to 0.0007, or 0.0004 to 0.0006.
[0183] In an optional implementation manner of this embodiment, the above x i The value of can be 20, 40, 60, 80, 100, 120, 140, 160, 180, 200, 220, 240, and its value range can preferably be 20-240, 40-220, 60-200, 80-180, 100-160, 120-140.
[0184] In an optional implementation manner of this embodiment, the chemically strengthened glass-ceramics satisfies the following tensile stress linear density relationship:
[0185] CTLD=A*E / (2*(1-2ν))*Δv%-B*CS / τ
[0186] Where F represents the tensile stress linear density, A and B are constants, E represents Young's modulus, ν represents Poisson's ratio, △v% represents the volume change ratio of the glass before and after chemical strengthening, CS represents the surface compressive stress, τ represents the relaxation time; and, 26000≤F≤34000MPa, 97≤E≤105GPa, 0<△v%<3%, 0≤τ≤1750h, 60 <A+B<80。
[0187] In an optional implementation manner of this embodiment, the value of the above F can be 26000, 27000, 28000, 29000, 30000, 31000, 32000, 33000, or 34000, and its value range can preferably be 27000-33000, 28000-32000, or 29000-31000.
[0188] In an optional implementation manner of this embodiment, the value of E can be 97, 98, 99, 100, 101, 102, 103, 104, or 105, and its value range can preferably be 98-104, 99-103, or 100-102.
[0189] In an optional implementation manner of this embodiment, the value of the above Δv% can be 0.5%, 1%, 1.5%, 2%, or 2.5%, and its value range can preferably be 0.5% to 2.5%, or 1% to 2%.
[0190] In an optional implementation manner of this embodiment, the value of the above-mentioned τ can be 0, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1750, and its value range can preferably be 100-1700, 200-1600, 300-1500, 400-1400, 500-1300, 600-1200, 700-1100, 800-1000.
[0191] In an optional implementation manner of this embodiment, the value of the above A+B can be 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, and its value range can preferably be 26-44, 27-43, 28-42, 29-41, 30-40, 31-39, 32-38, 33-37, 34-36.
[0192] In the above formula, τ represents the relaxation time, which is the characteristic time it takes for a material to undergo viscoelastic relaxation under stress. This is the local rearrangement of atoms and ions within the glass network, partially releasing stress. The inward diffusion of K+ or the reverse migration of Na+ reduces the concentration gradient, leading to stress decay. At high temperatures, glass exhibits viscoelastic properties, and stress relaxation occurs through microscopic flow, a dynamic process that represents stress decay.
[0193] Calculate τ according to the Maxwell model:
[0194]
[0195] Where η is the viscosity and E is the elastic modulus.
[0196] It is known that E is 102GPa at room temperature, but at high temperature, E decreases slightly but still remains at a high value, so the maximum value is taken for calculation;
[0197] Among them, the glass-ceramic is LAS system and the IOX temperature is 420℃~500℃, then at 420℃, η=10 15 pa*s, at 500℃, η=10 13.4 pa*s.
[0198] Then, in the embodiment of the present application, it can be obtained by calculation that τ at 420°C is 100800s=28h, and τ at 500°C is 2160s=0.6h. In summary, the preferred range of τ is as follows: 0.6≤τ≤28h.
[0199] There is a complex relationship between changes in ion concentration, crystal structure and stress measurement results after ion exchange. By studying the correlation between changes in ion concentration, crystal structure and stress measurement results in chemically strengthened microcrystalline glass, we can have a deeper understanding of the microscopic mechanism of the chemical strengthening process, guide the adaptive optimization of process parameters, and help achieve uniform stress distribution on the glass surface, reduce edge warping and other problems, and reduce stress relaxation.
[0200] Generally speaking, glass-ceramics obtained through the nucleation and crystallization processes typically have a relatively uniform crystal content at different depths from the surface, meaning that the crystal ratio at each depth in the glass is essentially the same. However, unlike traditional glass-ceramics, which have a uniform crystal ratio, this application uniquely considers the effects of decrystallization caused by ion exchange during the chemical strengthening process of glass-ceramics. The application studies the impact of the changing crystal content at different depths during the ion exchange process on the mechanical properties of the strengthened glass-ceramics.
[0201] The applicant's research found that in the chemically strengthened microcrystalline glass, the functional relationship formed by the crystal content at different depths is strongly correlated with the mechanical properties of the chemically strengthened microcrystalline glass. The more the trend of the crystal ratio change along the thickness direction of the glass conforms to the Boltzmann function relationship, the better the mechanical properties of the glass and the better its resistance to damage.
[0202] It's important to understand that the crystal content also characterizes the level of stress stored in the glass after chemical strengthening. A higher crystal content on the surface means lower energy storage, and in this case, the strength of the glass after the exchange may not meet the required mechanical properties. On the other hand, a lower crystal content on the surface means greater energy storage. While this enhances strength, it may also increase the risk of delayed failure or spontaneous explosion under environmental stress, while also keeping the stress level within the range where the glass's mechanical properties are optimal.
[0203] Based on this, an embodiment of the present application provides the above-mentioned crystal content relationship formula. The chemically strengthened microcrystalline glass that satisfies the setting of this relationship can make the crystal ratio change trend conform to the Boltzmann function relationship. Thanks to the Boltzmann distributed crystal layer of this embodiment, the glass has excellent anti-destructive ability when subjected to high-speed strain of large external forces (such as external forces generated by falling impacts), and the mechanical properties are effectively optimized.
[0204] The embodiment of the present application exemplarily provides a first type of microcrystalline glass before chemical strengthening, whose components, recorded in molar percentage, include: SiO2 greater than or equal to 60% and less than or equal to 78%; Al2O3 greater than or equal to 2% and less than or equal to 6.7%; Li2O greater than or equal to 16% and less than or equal to 24%; P2O5 greater than or equal to 0.1% and less than or equal to 2.2%; ZrO2 greater than or equal to 0 and less than or equal to 5%; RO greater than or equal to 0 and less than or equal to 5.3%, and RO includes at least one of CaO, MgO, ZnO, and BaO; Na2O greater than or equal to 0% and less than or equal to 5%; K2O greater than or equal to 0 and less than or equal to 4%; and a clarifier greater than or equal to 0 and less than or equal to 1%.
[0205] Among them, the preferred content of SiO2 is 66-71.28%, more preferably 66.5-70.8%, and further preferably 67.1-69.5%; the preferred content of Al2O3 is 3-5.5%, more preferably 3.5-5.2%, and further preferably 3.5-4.6%; the preferred content of P2O5 is 0.3-1.6%, more preferably 0.6-1.2%, and further preferably 0.8-1.1%; the preferred content of ZrO2 is 0-3. 7%, more preferably 0-2.6%, further preferably 0.6-2.6%; the preferred content of Na2O is 0-3.5%, more preferably 0-2.0%, further preferably 0-1.5%; the preferred content of K2O is 0-2%, more preferably 0-0.5%, further preferably 0-0.3%; the preferred content of Li2O is 18-23.5%, more preferably 20.5-23.5%, further preferably 21.5-23.5%. The alkaline earth metal oxides mentioned above are respectively comprised in the glass-ceramics of: greater than or equal to 0 and less than or equal to 4% CaO, greater than or equal to 0 and less than or equal to 4% MgO, greater than or equal to 0 and less than or equal to 4% ZnO, and greater than or equal to 0 and less than or equal to 4% BaO. The preferred content of CaO is 0-2.5%, more preferably 0-1.5%, and even more preferably 0.2-0.5%. The preferred content of MgO is 0-2.5%, more preferably 0-1%, and even more preferably 0-0.5%. The preferred clarifier is SnO2, with a preferred content of 0.05-0.5%, more preferably 0.05-0.2%, and even more preferably 0.05-0.15%. In addition, the microcrystalline glass may also include: B2O3 greater than or equal to 0 and less than or equal to 4.8%, and / or TiO2 greater than or equal to 0% and less than or equal to 4%, and / or Y2O3 greater than or equal to 0 and less than or equal to 4%, and / or La2O3 greater than or equal to 0 and less than or equal to 0.5%, wherein the preferred content of B2O3 is 0-3%, more preferably 0-1.6%, and further preferably 0-0.4%; the preferred content of TiO2 is 0-2.6%, more preferably 0-1.2%, and further preferably 0-0.6%; the preferred content of Y2O3 is 0-2%, more preferably 0-0.5%, and further preferably 0-0.3%; the preferred content of La2O3 is 0-2%, more preferably 0-0.5%, and further preferably 0-0.3%.
[0206] The chemically strengthened glass-ceramics obtained by ion exchange treatment of the glass-ceramics has crystal phases of lithium disilicate and petalite. On the one hand, the maximum ratio of lithium disilicate crystals in the Boltzmann distribution crystal layer is 33% to 39% (for example, about 33%, 34%, 35%, 36%, 37%, 38%, and 39%), and the minimum ratio of lithium disilicate crystals is 20% to 24% (for example, about 20%, 21%, 22%, 23%, and 24%). In addition, the maximum ratio of petalite crystals in the Boltzmann distribution crystal layer is 47% to 50% (for example, about 47%, 48%, 49%, and 50%), and the minimum ratio of petalite crystals is 34% to 38% (for example, about 34%, 35%, 36%, 37%, and 38%). On the other hand, the average grain size of the lithium silicate crystal phase is less than or equal to 32.5 to 39.3 nm, the average grain size of the petalite crystal phase is less than or equal to 24.6 to 29.1 nm, and the crystallinity is greater than or equal to 84.72%. Furthermore, the lithium disilicate crystalline phase meets the following indicators: the size of 98% of the grains in the lithium disilicate crystalline phase as a whole is less than or equal to 55 nm, the size of 95% of the grains in the lithium disilicate crystalline phase as a whole is less than or equal to 50 nm, and the size of 80% of the grains in the lithium disilicate crystalline phase as a whole is less than or equal to 45 nm; the petalite crystalline phase meets the following indicators: the size of 98% of the grains in the petalite crystalline phase as a whole is less than or equal to 45 nm, the size of 95% of the grains in the petalite crystalline phase as a whole is less than or equal to 40 nm, and the size of 80% of the grains in the petalite crystalline phase as a whole is less than or equal to 30 nm; the crystallinity is greater than or equal to 85.8%.
[0207] In addition, the chemically strengthened glass-ceramics satisfies the following crystal content relationship:
[0208] F(x)=W*(-a*(T*t) / (1+exp((x i -x0) / (dx)))
[0209] Wherein, F(x) represents the crystal ratio of chemically strengthened glass-ceramics at depth x, W represents the crystal content of chemically strengthened glass-ceramics before strengthening, a is a constant, T represents the temperature of the chemical strengthening salt bath, t represents the duration of ion exchange treatment, and x i represents the depth from the glass surface to i, x0 represents the depth of the glass surface; and, 20%<F(x)<50%, 30% <W<50%,0<a<0.001,0<x i <250μm.
[0210] Furthermore, the chemically strengthened glass-ceramics satisfies the following tensile stress linear density relationship:
[0211] CTLD=A*E / (2*(1-2ν))*Δv%-B*CS / τ
[0212] Wherein, F represents the tensile stress linear density, A and B are constants, E represents Young's modulus, ν represents Poisson's ratio, △v% represents the volume change ratio of glass before and after chemical strengthening, CS represents the surface compressive stress, τ represents the relaxation time; and, 26000≤F≤30000MPa, 97≤E≤105GPa, 0<△v%<3%, 360≤τ≤420min, 60 <A+B<80。
[0213] The embodiment of the present application exemplarily provides a second type of microcrystalline glass before chemical strengthening, whose components, recorded in molar percentage, include: SiO2 greater than or equal to 60% and less than or equal to 78%; Al2O3 greater than or equal to 1.5% and less than or equal to 5.5%; Li2O greater than or equal to 18% and less than or equal to 26.8%; P2O5 greater than or equal to 0.1 and less than or equal to 2.5%; ZrO2 greater than or equal to 0 and less than or equal to 5%; RO greater than or equal to 0 and less than or equal to 3.4%, and RO includes at least one of CaO, MgO, ZnO, and BaO; Na2O greater than or equal to 0% and less than or equal to 6.5%; K2O greater than or equal to 0 and less than or equal to 4%; and a clarifier greater than or equal to 0 and less than or equal to 1%.
[0214] Among them, the preferred content of SiO2 is 61.7-75.4%, more preferably 62.4-71.3%, and further preferably 64.7-68.3%; the preferred content of Al2O3 is 2-5.5%, more preferably 2-4.2%, and further preferably 2.5-3.5%; the preferred content of P2O5 is 0.6-2.5%, more preferably 0.6-1.5%, and further preferably 1.0-1.4%; the preferred content of ZrO2 is 0-3.7% , the more preferred content is 0-2.6%, and the further preferred content is 0.6-2.6%; the preferred content of Na2O is 0-4.8%, the more preferred content is 0-3.1%, and the further preferred content is 1.0-3.1%; the preferred content of K2O is 0-2%, the more preferred content is 0-1.2%, and the further preferred content is 0-0.6%; the preferred content of Li2O is 18-25.8%, the more preferred content is 22.2-25.8%, and the further preferred content is 23.4-24.4%. The alkaline earth metal oxides mentioned above are respectively comprised in the glass-ceramics of: greater than or equal to 0 and less than or equal to 4% CaO, greater than or equal to 0 and less than or equal to 4% MgO, greater than or equal to 0 and less than or equal to 4% ZnO, and greater than or equal to 0 and less than or equal to 4% BaO. The preferred content of CaO is 0-2.5%, more preferably 0-1.5%, and even more preferably 0-0.5%. The preferred content of MgO is 0-2.5%, more preferably 0-1.5%, and even more preferably 0-0.5%. The preferred clarifier is SnO2, with a preferred content of 0.05-0.5%, more preferably 0.05-0.2%, and even more preferably 0.05-0.15%. In addition, the microcrystalline glass may also include: B2O3 greater than or equal to 0 and less than or equal to 4.8%, and / or TiO2 greater than or equal to 0% and less than or equal to 4%, and / or Y2O3 greater than or equal to 0 and less than or equal to 4%, and / or La2O3 greater than or equal to 0 and less than or equal to 0.5%, wherein the preferred content of B2O3 is 0-3%, more preferably 0-1.6%, and further preferably 0-0.4%; the preferred content of TiO2 is 0-2.6%, more preferably 0-1.2%, and further preferably 0-0.6%; the preferred content of Y2O3 is 0-2%, more preferably 0-0.5%, and further preferably 0-0.3%; the preferred content of La2O3 is 0-2%, more preferably 0-0.5%, and further preferably 0-0.3%.
[0215] The chemically strengthened glass-ceramics obtained after ion exchange treatment based on this glass-ceramics has a crystalline phase of lithium disilicate. On the one hand, the maximum proportion of lithium disilicate crystals in the Boltzmann distribution crystal layer is 50% to 75%, and the minimum proportion of lithium disilicate crystals is 61% to 65%. On the other hand, the lithium disilicate crystalline phase meets the following indicators: the average grain size is less than or equal to 38 to 45.7nm, and the crystallinity is greater than or equal to 56.38%. Furthermore, the lithium disilicate crystalline phase meets the following indicators: 98% of the grains in the entire crystal phase have a size less than or equal to 60nm, 95% of the grains in the entire crystal phase have a size less than or equal to 55nm, and 80% of the grains in the entire crystal phase have a size less than or equal to 50nm; the crystallinity is greater than or equal to 61.22%.
[0216] In addition, the chemically strengthened glass-ceramics satisfies the following crystal content relationship:
[0217] F(x)=W*(-a*(T*t) / (1+exp((x i -x0) / (dx)))
[0218] Wherein, F(x) represents the crystal ratio of chemically strengthened glass-ceramics at depth x, W represents the crystal content of chemically strengthened glass-ceramics before strengthening, a is a constant, T represents the temperature of the chemical strengthening salt bath, t represents the duration of ion exchange treatment, and x i represents the depth from the glass surface to i, x0 represents the depth of the glass surface; and, 55%<F(x)<75%, 65% <W<75%,0<a<0.001,0<x i <250μm.
[0219] Furthermore, the chemically strengthened glass-ceramics satisfies the following tensile stress linear density relationship:
[0220] CTLD=A*E / (2*(1-2ν))*Δv%-B*CS / τ
[0221] Where F represents the tensile stress linear density, A and B are constants, E represents Young's modulus, ν represents Poisson's ratio, △v% represents the volume change ratio of the glass before and after chemical strengthening, CS represents the surface compressive stress, τ represents the relaxation time; and, 31000≤F≤34000MPa, 97≤E≤105GPa, 0<△v%<3%, 0.6≤τ≤28h, 60 <A+B<80。
[0222] It is worth mentioning that the chemically strengthened glass-ceramics of this embodiment meets at least one of the following performance indicators: Vickers hardness greater than or equal to 655 kgf / mm 2 , fracture toughness greater than or equal to 1.2Mpa·m 1 / 2, Young's modulus greater than or equal to 98.38 GPa, shear modulus greater than or equal to 39.35 GPa, |B| value less than or equal to 0.53% when the thickness is 0.5 mm, haze less than or equal to 0.13%, transmittance relative to visible light with a wavelength of 550 nm is greater than or equal to 91%, the nine-point drop test height based on a 32g steel ball when the thickness is 0.5 mm is 980~1290 mm, the maximum bending strength is 1052~1200 MPa, the drop test height of the whole machine based on 80 mesh sandpaper is 85±520 mm, and the drop test height of the whole machine based on 180 mesh sandpaper is 1200~1600 mm.
[0223] Accordingly, an embodiment of the present application further provides a method for preparing chemically strengthened glass-ceramics, which specifically includes:
[0224] Step A: Mix the raw materials uniformly according to the glass formula, melt them at a preset melting temperature and melting time, and then form and anneal them to obtain glass raw materials;
[0225] Step B, heat-treating the glass raw material to obtain glass-ceramics;
[0226] Step C: Immersing the glass-ceramics in a chemically strengthened salt bath for ion exchange treatment to obtain chemically strengthened glass-ceramics.
[0227] The components of the above glass formulation, measured in mole percentage, include: SiO2 greater than or equal to 60% and less than or equal to 78%; Al2O3 greater than or equal to 1.5% and less than or equal to 6.7%; Li2O greater than or equal to 16% and less than or equal to 26.8%; P2O5 greater than or equal to 0.1% and less than or equal to 2.5%; ZrO2 greater than or equal to 0 and less than or equal to 5%; RO greater than or equal to 0 and less than or equal to 5.3%, wherein RO includes at least one of CaO, MgO, ZnO, and BaO; Na2O greater than or equal to 0% and less than or equal to 6.5%; K2O greater than or equal to 0 and less than or equal to 4%; and fining agent greater than or equal to 0 and less than or equal to 1%.
[0228] The chemically strengthened microcrystalline glass includes two Boltzmann distributed crystal layers with preset thicknesses extending inward from two outer surfaces, and a uniformly distributed crystal layer located between the two Boltzmann distributed crystal layers. The thickness of each Boltzmann distributed crystal layer is greater than 0 and less than or equal to 200 μm. The crystal ratio of each Boltzmann distributed crystal layer gradually increases from the outer surface to the inner part of the chemically strengthened microcrystalline glass. The maximum crystal ratio of the Boltzmann distributed crystal layer is 50% to 89%, and the minimum crystal ratio is 30% to 65%.
[0229] In actual applications, glass raw materials are first prepared according to the components and contents of the microcrystalline glass provided in the aforementioned embodiments, and the glass raw materials are evenly mixed and melted at 1350-1550°C. The precursor glass is then obtained after clarification, homogenization, forming, and annealing. Then, the precursor glass is crystallized using a two-stage heat treatment method. The first step of the heat treatment is nucleation treatment, and the second step of the heat treatment is crystallization treatment. Subsequently, the glass is cooled to room temperature to obtain microcrystalline glass that meets the expected crystallinity, grain size, and crystal phase ratio.
[0230] Among them, corresponding to the first type of microcrystalline glass provided in the aforementioned embodiment, its heat treatment process may include: placing the glass raw material in a crystallization furnace, heating it to 500-610°C at a heating rate greater than or equal to 6°C / min, and then keeping it warm for 200-300 minutes, then heating it to 655-800°C at a heating rate greater than or equal to 6°C / min, and then keeping it warm for 60-120 minutes, and finally cooling it at a cooling rate less than or equal to 2°C / min.
[0231] Corresponding to the second type of microcrystalline glass provided in the aforementioned embodiment, its heat treatment process may include: placing the glass raw material in a crystallization furnace, heating it to 560-590°C at a heating rate of 8-12°C / min and then keeping it warm for 220-250 minutes, then heating it to 750-790°C at a heating rate of 8-12°C / min and then keeping it warm for 70-90 minutes, and finally cooling it at a cooling rate less than or equal to 2°C / min.
[0232] Therefore, by heat-treating glass raw materials of different components using different heat treatment processes, desired types of crystal phases, desired crystal ratios, grain size distributions, etc. can be obtained.
[0233] It is worth mentioning that the microcrystalline glass obtained in the above step B can be further cold-processed, that is, through shaping, multi-wire cutting, CNC, grinding, rough grinding, fine polishing, cleaning and other processes, to obtain microcrystalline glass with a thickness of 0.35 to 1 mm.
[0234] In addition, corresponding to the second type of microcrystalline glass provided in the aforementioned embodiment, this embodiment can also perform hot bending treatment on the microcrystalline glass, wherein the pressure of the hot bending workstation is 0.7~1.1MPa, and the operating time of a single workstation is 70~110s.
[0235] In an optional implementation manner of this embodiment, the hot bending treatment needs to go through four preheating workstations, three hot pressing workstations and two cooling workstations; among them, the operating temperature of the first preheating workstation is 430~470℃, the operating temperature of the second preheating workstation is 530~570℃, the operating temperature of the third preheating workstation is 630~670℃, the operating temperature of the fourth preheating workstation is 710~730℃, the operating temperature of the first hot pressing workstation is 740~760℃, the operating temperature of the second hot pressing workstation is 740~760℃, the operating temperature of the third hot pressing workstation is 580~620℃, the operating temperature of the first cooling workstation is 430~470℃, and the operating temperature of the second cooling workstation is 280~320℃.
[0236] In this embodiment, when chemically strengthening the microcrystalline glass, the chemical strengthening salt bath includes, in mass percentage, the following: KNO3 greater than or equal to 9.99% and less than or equal to 89.99%, NaNO3 greater than or equal to 9.99 and less than or equal to 89.99%; preferably, KNO3 greater than or equal to 9.99% and less than or equal to 39.99%, NaNO3 greater than or equal to 59.99 and less than or equal to 89.99%, LiNO3 greater than or equal to 0.03% and less than or equal to 0.1%, the temperature of the chemical strengthening salt bath is 390-600°C, and the duration of the ion exchange treatment is 4-10 hours.
[0237] In order to create Boltzmann distributed crystals in glass-ceramics, the present invention provides a method for obtaining compressive stress by forming Boltzmann crystal distribution and ion exchange (IOX). This is achieved by IOX for a certain period of time within a suitable temperature and viscosity range. By giving appropriate temperature and viscosity, some crystals can participate in IOX, which in turn causes the crystal structure to be destroyed, and after a sufficiently long time, these "destroyed crystals" are allowed to re-form a complete structure with the glass phase. This avoids the situation where the temperature is too high, the viscosity is too low, and too many crystals disappear, resulting in the inability to achieve a gradient distribution of the Boltzmann distribution, thereby failing to achieve a gradual mechanical change to improve strength.
[0238] In this application, a Boltzmann distribution is formed by controlling the characteristic temperature range during the chemical strengthening process. Specifically, the temperature of the chemical strengthening salt bath is 390-600°C, more preferably 500-550°C. When the strengthening temperature of the salt bath is below the glass transition temperature (Tg), the glass viscosity is very high, making it difficult to change the distribution of existing crystals. In this application, by setting the temperature to 500-550°C, higher than the glass transition temperature (Tg), the crystal distribution in the glass is changed, making it easier to produce chemically strengthened glass with a crystal layer having a composite Boltzmann function distribution.
[0239] Chemical strengthening involves placing glass-ceramics in a salt bath for ion exchange, which results in the formation of compressive and tensile stress layers. The salt bath in this embodiment is a mixed salt bath. Compared to traditional multiple strengthening processes, this embodiment achieves multiple ion exchange events between the salt bath and the glass-ceramics in a single strengthening step, improving chemical strengthening efficiency and reducing salt bath usage. The resulting chemically strengthened glass-ceramics exhibit a deeper compressive stress layer and higher surface compressive stress.
[0240] It is worth mentioning that for chemically strengthened glass-ceramics, after being taken out of the salt bath, the surface residual substances can be cleaned first, and then the surface can be re-grinded using a flat grinder. The relevant parameters of the re-grinding process are set as follows: the surface is white, the hardness is 75, the upper and lower grinding discs are both 10 rpm, and the grinding powder concentration is 1.13 g / cm 3 , pressure 150-250kg, re-grinding number of 100-300 laps. Finally, the chemically strengthened micro-ceramic glass can be cleaned with a neutral cleaning agent with a pH of 7-9 to obtain chemically strengthened micro-ceramic glass products.
[0241] Corresponding to the first type of microcrystalline glass provided in the aforementioned embodiment, the chemically strengthened microcrystalline glass obtained after ion exchange treatment meets the following performance indicators: the surface compressive stress value is 255~280MPa, the compressive stress value at a depth of 50μm from the surface is 105~112MPa, the compressive stress value at a depth of 80μm from the surface is 65~70MPa, the depth of the compressive stress layer is 121~135μm, the absolute value of the maximum tensile stress is 100~110MPa, and the absolute value of the average tensile stress is 59~63Mpa.
[0242] Corresponding to the second type of microcrystalline glass provided in the aforementioned embodiment, the chemically strengthened microcrystalline glass obtained after ion exchange treatment meets the following performance indicators: the surface compressive stress value is 240~276MPa, the compressive stress value at a depth of 50μm from the surface is 102~125MPa, the compressive stress value at a depth of 80μm from the surface is 65~75MPa, the depth of the compressive stress layer is 113~130μm, the absolute value of the maximum tensile stress is 105~108MPa, and the absolute value of the average tensile stress is 58~63MPa.
[0243] Next, in order to illustrate the technical effects of the microcrystalline glass and chemically strengthened microcrystalline glass of this embodiment, this application conducted experiments on microcrystalline glasses with different component contents to determine the characteristics of each microcrystalline glass. Examples 1 to 4 in Table 1 and Examples 5 to 6 in Table 2 correspondingly show the crystal ratio data of the aforementioned first microcrystalline glass varying with depth, Examples 1 to 4 in Table 3 show the relevant test conditions and test data of the above-mentioned first microcrystalline glass of this application at different component contents, Examples 1 to 4 in Table 4 and Examples 5 to 6 in Table 5 correspondingly show the sodium-potassium ion concentration data of the above-mentioned first microcrystalline glass after chemical strengthening varying with depth; Examples 7 to 14 in Table 6 correspondingly show the crystal ratio data of the above-mentioned second microcrystalline glass varying with depth, Examples 1 to 8 in Table 7 show the relevant test conditions and test data of the above-mentioned second microcrystalline glass of this application at different component contents, and Examples 7 to 10 in Table 8 correspondingly show the sodium-potassium ion concentration data of the above-mentioned second microcrystalline glass after chemical strengthening varying with depth.
[0244] Table 1
[0245]
[0246] Table 2
[0247]
[0248]
[0249] Table 3
[0250]
[0251]
[0252] Table 4
[0253]
[0254]
[0255] Table 5
[0256]
[0257]
[0258] Table 6
[0259]
[0260] Table 7
[0261]
[0262]
[0263]
[0264]
[0265] Table 8
[0266]
[0267]
[0268] Tables 1 and 6 both provide data on the variation of crystal ratio with depth that conforms to the aforementioned crystal content relationship. Comparison of the experimental data for the examples and comparative examples in Tables 3 and 7 indicates that the variation in crystal ratio in the glass-ceramics of the present application shows a trend of gradually increasing from the surface toward the interior of the glass and maintaining stability after reaching a maximum depth. In other words, the glass obtained after chemical strengthening includes two Boltzmann distributed crystal layers extending inward from the two outer surfaces to a predetermined thickness, and a uniformly distributed crystal layer located between the two Boltzmann distributed crystal layers. The crystal ratio in the Boltzmann distributed crystal layers gradually increases from the outer surface to the interior of the glass-ceramics, and the increasing trend of the crystal ratio conforms to the Boltzmann function relationship.
[0269] Mechanical performance tests revealed that the height of a nine-point drop of a 32g steel ball, as well as the drop height of the entire device using 180-grit and 80-grit sandpaper, for the improved glass-ceramics provided in all examples exceeded those of the conventional glass-ceramics provided in the comparative examples. Therefore, it can be seen that when the crystal content in the glass-ceramics conforms to the Boltzmann function graph, the glass-ceramics with both a Boltzmann-distributed crystal layer and a uniform crystal layer exhibits greater overall resistance to damage when subjected to large external forces and high-speed strain, exhibiting higher resistance to drops and falls, and exhibiting excellent mechanical properties.
[0270] Table 4 and Table 8 are the concentration changes in ion exchange. The chemical strengthening mentioned in this application is the exchange process between large-volume ions and small-volume ions. Due to the exchange between the two, the larger K + with Na + When ions are replaced to the positions of the originally smaller ions, the concentration of ions in the glass will change accordingly, and the ion exchange process will also cause the volume of the glass to change. Correspondingly, the ion exchange will also affect the crystal content in the glass, because the ion exchange process will cause crystal decrystallization. After experiments, the applicant found that the concentration change of the ion content in this application is consistent with the Boltzmann function graph, and the corresponding crystal content change is also consistent with the Boltzmann function graph. The two directions are opposite, one gradually increases from the surface to the inside, and the other gradually increases from the inside to the surface.
[0271] In summary, this application correlates changes in ion concentration and crystal structure with stress measurements, establishing models or empirical formulas to quantitatively describe the effects of ion exchange concentration and crystal changes on surface stress. By directly reflecting stress by studying changes in ion concentration and crystal structure before and after chemical strengthening, this research not only helps optimize chemical strengthening processes and improve glass performance, but also promotes new material development and basic scientific research. This research has important practical and theoretical value for both industrial production and scientific research.
[0272] It is also worth mentioning that due to the above-mentioned performance advantages of the chemically strengthened microcrystalline glass provided in the embodiments of the present application, it can be widely used in the production of protective covers of electronic devices, optical elements, photovoltaic devices or windows of household appliances.
[0273] Finally, it should be noted that in the above embodiments, the description of each embodiment has its own focus. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0274] The above is a description of the chemically strengthened microcrystalline glass and its preparation method provided in this application. For those skilled in the art, based on the ideas of the embodiments of this application, equivalent substitutions made in the specific implementation methods and application scopes should all be covered by the scope of the claims of this application. In summary, the content of this specification should not be understood as a limitation on the scheme of this application.
Claims
1. A chemically strengthened glass-ceramic, characterized in that: The chemically strengthened glass-ceramics include two Boltzmann distribution crystal layers respectively extending inwards from two outer surfaces by a preset thickness, and a uniformly distributed crystal layer between the two Boltzmann distribution crystal layers. The thickness of each Boltzmann distribution crystal layer is greater than 0 and less than or equal to 200 μm; the crystal ratio of each Boltzmann distribution crystal layer gradually increases from the outer surface to the interior of the chemically strengthened glass-ceramics, and the maximum crystal ratio of the Boltzmann distribution crystal layer is 50% - 89%, and the minimum crystal ratio is 30% - 65%.
2. The chemically strengthened glass-ceramics according to claim 1, wherein: At least a part of the Boltzmann distribution crystal layer has a compressive stress, and the compressive stress is greater than 50 and less than or equal to 270 MPa.
3. The chemically strengthened glass-ceramics according to claim 1, wherein: The thickness of each Boltzmann distribution crystal layer is 100 - 200 μm.
4. The chemically strengthened glass-ceramics according to claim 1, wherein The measurement tolerance of the crystal ratio in the uniformly distributed crystal layer is ±5%.
5. The chemically strengthened glass-ceramics according to claim 1, wherein: The uniformly distributed crystal layer has a tensile stress, and its crack tip opening displacement CTLD is greater than or equal to 26000 MPa.
6. The chemically strengthened glass-ceramics according to claim 5, wherein: The crystal phases of the chemically strengthened glass-ceramics include one or more of lithium disilicate, spodumene, quartz and quartz solid solution, spodumene, lithium metasilicate, nepheline, spinel, wollastonite, cordierite, etc.
7. The chemically strengthened glass-ceramics according to claim 1, wherein The chemically strengthened glass-ceramics are obtained by ion exchange treatment of glass-ceramics based on a preset composition. The composition of the glass-ceramics is in mole percentage and includes: SiO2 greater than or equal to 60% and less than or equal to 78%; Al2O3 greater than or equal to 1.5% and less than or equal to 6.7%; Li2O greater than or equal to 16% and less than or equal to 26.8%; P2O5 greater than or equal to 0.1 and less than or equal to 2.5%; ZrO2 greater than or equal to 0 and less than or equal to 5%; RO greater than or equal to 0 and less than or equal to 5.3%, and RO includes at least one of CaO, MgO, ZnO, BaO; and, Na2O greater than or equal to 0% and less than or equal to 6.5%; K2O greater than or equal to 0 and less than or equal to 4%; 8. The chemically strengthened glass-ceramics according to claim 1, wherein clarifying agent greater than or equal to 0 and less than or equal to 1%. F(x)=W*(-a*(T*t) / (1+exp((x i -x0) / (dx))) Wherein, F(x) represents the crystal ratio of the chemically strengthened glass-ceramics at depth x, W represents the crystal content of the chemically strengthened glass-ceramics before strengthening, a is a constant, T represents the temperature of the chemical strengthening salt bath, t represents the duration of the ion exchange treatment, and x i represents the depth from the glass surface to i, x0 represents the depth of the glass surface; and, 20%<F(x)<75%, 30% <W<75%,0<a<0.001,0<x i <250μm.
9. The chemically strengthened glass-ceramics according to claim 1, wherein: The chemically strengthened glass-ceramics satisfy the following crystal content relationship:[[]]END The chemically strengthened glass-ceramics satisfy the following crack tip opening displacement relationship:[[]]END CTLD = A*E / (2*(1 - 2ν))*△v% - B*CS / τ 10. The chemically strengthened glass-ceramics according to claim 7, wherein: Where, CTLD represents the crack tip opening displacement, A and B are constants, E represents Young's modulus, ν represents Poisson's ratio, △v% represents the glass volume change ratio before and after chemical strengthening, CS represents the surface compressive stress, τ represents the relaxation time; and, 26000 ≤ F ≤ 34000 MPa, 97 ≤ E ≤ 105 GPa, 0 < △v% < 3%, 0 ≤ τ ≤ 1750 h, 60 < A + B < 80, A is the extrusion coefficient, and B is the relaxation coefficient. The chemically strengthened glass-ceramics are obtained by ion exchange treatment of glass-ceramics based on a preset composition. The composition of the glass-ceramics is in mole percentage and includes:[[]]END SiO2 greater than or equal to 60% and less than or equal to 78%; Al2O3 greater than or equal to 2% and less than or equal to 6.7%; 16% or more and 24% or less of Li2O; P2O5 greater than or equal to 0.1 and less than or equal to 2.2%; ZrO2 greater than or equal to 0 and less than or equal to 5%; RO is greater than or equal to 0 and less than or equal to 5.3%, and RO includes at least one of CaO, MgO, ZnO, and BaO; greater than or equal to 0% and less than or equal to 5% Na2O; K2O greater than or equal to 0 and less than or equal to 4%; Greater than or equal to 0 and less than or equal to 1% of clarifier.
11. The chemically strengthened glass-ceramics according to claim 7, wherein: The chemically strengthened glass-ceramics is obtained by subjecting glass-ceramics of preset components to ion exchange treatment. The components of the glass-ceramics, expressed in molar percentage, include: SiO2 greater than or equal to 60% and less than or equal to 78%; 1.5% or more and 5.5% or less of Al2O3; 18% or more and 26.8% or less of Li2O; P2O5 greater than or equal to 0.1 and less than or equal to 2.5%; ZrO2 greater than or equal to 0 and less than or equal to 5%; RO is greater than or equal to 0 and less than or equal to 3.4%, and RO includes at least one of CaO, MgO, ZnO, and BaO; greater than or equal to 0% and less than or equal to 6.5% Na2O; K2O greater than or equal to 0 and less than or equal to 4%; Greater than or equal to 0 and less than or equal to 1% of clarifier.
12. The chemically strengthened glass-ceramics according to claim 10, wherein: The crystalline phases of the chemically strengthened glass-ceramics include lithium disilicate and petalite.
13. The chemically strengthened glass-ceramics according to claim 12, wherein: The maximum ratio of lithium disilicate crystals in the Boltzmann distribution crystal layer is 33% to 39%, and the minimum ratio of lithium disilicate crystals is 20% to 24%. In addition, the maximum ratio of petalite crystals in the Boltzmann distribution crystal layer is 47% to 50%, and the minimum ratio of petalite crystals is 34% to 38%.
14. The chemically strengthened glass-ceramics according to claim 12, wherein: The average grain size of the lithium disilicate crystal phase is less than or equal to 32.5-39.3 nm, the average grain size of the petalite crystal phase is less than or equal to 24.6-29.1 nm, and the crystallinity is greater than or equal to 84.72%.
15. The chemically strengthened glass-ceramics according to claim 14, wherein: The lithium disilicate crystalline phase meets the following indicators: 98% of the grains in the lithium disilicate crystalline phase have a size of less than or equal to 55 nm, 95% of the grains in the lithium disilicate crystalline phase have a size of less than or equal to 50 nm, and 80% of the grains in the lithium disilicate crystalline phase have a size of less than or equal to 45 nm; The petalite crystalline phase meets the following indicators: 98% of the grains in the petalite crystalline phase have a size of less than or equal to 45 nm, 95% of the grains in the petalite crystalline phase have a size of less than or equal to 40 nm, and 80% of the grains in the petalite crystalline phase have a size of less than or equal to 30 nm; The crystallinity is greater than or equal to 85.8%.
16. The chemically strengthened glass-ceramics according to claim 11, wherein The crystal phase of the chemically strengthened glass-ceramics is lithium disilicate; the maximum ratio of lithium disilicate crystals in the Boltzmann distribution crystal layer is 50% to 75%, and the minimum ratio of lithium disilicate crystals is 61% to 65%.
17. The chemically strengthened glass-ceramics according to claim 16, wherein: The lithium disilicate crystal phase meets the following criteria: the average grain size is less than or equal to 38 - 45.7 nm, and the crystallinity is greater than or equal to 56.38%.
18. The chemically strengthened glass-ceramics according to claim 17, wherein: The lithium disilicate crystal phase meets the following criteria: the size of 98% of the grains in the overall crystal phase is less than or equal to 60 nm, the size of 95% of the grains in the overall crystal phase is less than or equal to 55 nm, and the size of 80% of the grains in the overall crystal phase is less than or equal to 50 nm; the crystallinity is greater than or equal to 61.22%.
19. The chemically strengthened glass-ceramics according to claim 12, wherein: The chemically strengthened glass-ceramics satisfies the following crystal content relationship: F(x)=W*(-a*(T*t) / (1+exp((x i -x0) / (dx))) Wherein, F(x) represents the crystal ratio of the chemically strengthened glass-ceramics at depth x, W represents the crystal content of the chemically strengthened glass-ceramics before strengthening, a is a constant, T represents the temperature of the chemical strengthening salt bath, t represents the duration of the ion exchange treatment, and x i represents the depth from the glass surface to i, x0 represents the depth of the glass surface; and, 20%<F(x)<50%, 30% <W<50%,0<a<0.001,0<x i <250μm.
20. The chemically strengthened glass-ceramics according to claim 15, wherein The chemically strengthened glass-ceramics satisfies the following crystal content relationship: F(x)=W*(-a*(T*t) / (1+exp((x i -x0) / (dx))) Wherein, F(x) represents the crystal ratio of the chemically strengthened glass-ceramics at depth x, W represents the crystal content of the chemically strengthened glass-ceramics before strengthening, a is a constant, T represents the temperature of the chemical strengthening salt bath, t represents the duration of the ion exchange treatment, and x i represents the depth from the glass surface to i, x0 represents the depth of the glass surface; and, 55%<F(x)<75%, 65% <W<75%,0<a<0.001,0<x i <250μm.
21. The chemically strengthened glass-ceramics according to claim 10, wherein The chemically strengthened glass-ceramics satisfies the following surface compressive stress line density relationship: CTLD = A * E / (2 * (1 - 2ν)) * △v% - B * CS / τ Where, F represents the surface compressive stress line density, A and B are constants, E represents Young's modulus, ν represents Poisson's ratio, △v% represents the glass volume change ratio before and after chemical strengthening, CS represents the surface compressive stress, τ represents the relaxation time; and, 26000 ≤ F ≤ 30000 MPa, 97 ≤ E ≤ 105 GPa, 0 < △v% < 3%, 0.6 ≤ τ ≤ 28 h, 60 < A + B < 80, A is the extrusion coefficient, B is the relaxation coefficient.
22. The chemically strengthened glass-ceramics according to claim 11, wherein The chemically strengthened glass-ceramics satisfies the following surface compressive stress line density relationship: CTLD = A * E / (2 * (1 - 2ν)) * △v% - B * CS / τ Where, F represents the surface compressive stress line density, A and B are constants, E represents Young's modulus, ν represents Poisson's ratio, △v% represents the glass volume change ratio before and after chemical strengthening, CS represents the surface compressive stress, τ represents the relaxation time; and, 31000 ≤ F ≤ 34000 MPa, 97 ≤ E ≤ 105 GPa, 0 < △v% < 3%, 0.6 ≤ τ ≤ 28 h, 60 < A + B < 80, A is the extrusion coefficient, B is the relaxation coefficient.
23. A method for preparing chemically strengthened glass-ceramics, characterized in that: Including: Mix the raw materials evenly according to the glass formula and melt them at a preset melting temperature and melting duration, and then obtain the glass raw material after forming and annealing; Heat-treat the glass raw material to obtain glass-ceramics; Immerse the glass-ceramics in a chemical strengthening salt bath for ion exchange treatment to obtain chemically strengthened glass-ceramics; wherein, the chemically strengthened glass-ceramics includes two Boltzmann distribution crystal layers extending inward from two outer surfaces by a preset thickness respectively, and a uniformly distributed crystal layer between the two Boltzmann distribution crystal layers, the thickness of each Boltzmann distribution crystal layer is greater than 0 and less than or equal to 200 μm; the crystal ratio of each Boltzmann distribution crystal layer gradually increases from the outer surface to the inside of the chemically strengthened glass-ceramics, the maximum crystal ratio of the Boltzmann distribution crystal layer is 50% - 89%, and the minimum crystal ratio is 30% - 65%.
24. The preparation method according to claim 23, characterized in that The chemical strengthening salt bath comprises, by mass percentage, 9.99% or more and 89.99% or less of KNO 3 , 9.99% or more and 89.99% or less of NaNO 3 , and 0.03% or more and 0.1% or less of LiNO 3 .
25. The preparation method according to claim 24, characterized in that The temperature of the chemical strengthening salt bath is 390 to 600° C., and the duration of the ion exchange treatment is 0.5 to 14 hours.
Citation Information
Patent Citations
Ion exchanged glass-ceramic article
CN111954646A
Ultrathin glass ceramic article and method for producing ultrathin glass ceramic article
CN112839910A
Microcrystalline glass, chemically strengthened microcrystalline glass, preparation methods of microcrystalline glass and chemically strengthened microcrystalline glass, and electronic equipment
CN112919812A
Glass ceramic, tempered glass and preparation method and application thereof
CN114671618A
Glass-ceramic, glass-ceramic precursor, and preparation method for glass-ceramic
WO2024088186A1